2023
DOI: 10.1111/jcmm.17823
|View full text |Cite
|
Sign up to set email alerts
|

A negative feedback loop between KLF9 and the EMT program dictates metastasis of hepatocellular carcinoma

Abstract: Metastasis is the primary cause of death of hepatocellular carcinoma (HCC), while the mechanism underlying this severe disease remains largely unclear. The Kruppel‐like factor (KLF) family is one of the largest transcription factor families that control multiple physiologic and pathologic processes by governing the cellular transcriptome. To identify metastatic regulators of HCC, we conducted gene expression profiling on the MHCC97 cell series, a set of subclones of the original MHCC97 that was established by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In line with this, forced liver tumor expression of KLF9 in nude mice caused the regression of tumors accompanied by increased apoptosis and the decreased proliferation of xenografts [200]. In addition, a recent study found that over-expression of KLF9 caused suppression of metastasis of HCC tumor cells, whereas knock-down of KLF9 caused the opposite effects, ascribed, in part, to KLF9 repression of the EMT pathway [201]. KLF9 is a suppressor of oxidative stress and inflammation in the livers of high fat-fed mice [147], effects that are predicted to be tumor-preventive.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 69%
See 1 more Smart Citation
“…In line with this, forced liver tumor expression of KLF9 in nude mice caused the regression of tumors accompanied by increased apoptosis and the decreased proliferation of xenografts [200]. In addition, a recent study found that over-expression of KLF9 caused suppression of metastasis of HCC tumor cells, whereas knock-down of KLF9 caused the opposite effects, ascribed, in part, to KLF9 repression of the EMT pathway [201]. KLF9 is a suppressor of oxidative stress and inflammation in the livers of high fat-fed mice [147], effects that are predicted to be tumor-preventive.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 69%
“…KLF9 mRNA and protein levels are significantly lower in HCC tissue than in normal non-tumor liver tissue [199][200][201]. In HepG2 human liver cancer cells, the over-expression of KLF9 (by transfection) resulted in decreased proliferation and increased apoptosis [199,200].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%